Analisis dan Faktor-faktor yang Mempengaruhi Kemampuan Berpikir Kritis Peserta Didik Pada Materi Sistem Pencernaan Kelas VIII SMP Negeri 41 Medan - Melisa Karen; Melva Silitonga (CV.ITTC INDONESIA, 2024)
This research aims to analyze critical thinking abilities and determine the faktors that influence students' critical thinking abilities in class VIII digestive system material at SMP Negeri 41 Medan for the 2023/2024 academic year. This type of research is descriptive with mixed methods. The population in the study consisted of 8 classes and the sample consisted of 2 classes, namely classes VIII-2 and VIII-4, totaling 55 people. The sampling technique used was purposive sampling. Research data was collected using an essay test instrument consisting of 12 questions, an interview instrument consisting of 7 questions, and a learning tool observation sheet. The research results show that students' critical thinking abilities can be categorized as low with an average percentage score of 44.18. Faktors that influence students' critical thinking abilities are situational and dispositional faktors. The most influential situational faktor is involvement, while the most influential dispositional faktor is learning methods.